Self-made man one woman's journey into manhood and back again - Vincent, Norah (Viking, 2006)
For more than a year and a half Vincent ventured into the world as Ned, with an ever-present five o'clock shadow and a crew cut--a perfect disguise that enabled her to observe the world of men as an insider. With her buddies on the bowling league she enjoyed the rough and rewarding embrace of male camaraderie; a stint in a high-octane sales job taught her the gut-wrenching pressures endured by men who would do anything to succeed; she frequented sex clubs, dated women hungry for love but bitter about men, and infiltrated all-male communities including a men's therapy group and even a monastery. She ended her journey astounded--and exhausted--by the rigid codes and rituals of masculinity.--From publisher description.